2006
DOI: 10.1021/ol053092b
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (−)-Dactylolide

Abstract: [reaction: see text] The enantioselective total synthesis of (-)-dactylolide is reported. The absolute stereochemistry of the tetrahydropyran was established by catalytic asymmetric Jacobsen hetero-Diels-Alder reaction. The remote C19 stereocenter was introduced by a sequence of chelation-controlled Grignard addition and Ireland-Claisen rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 29 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…20 As shown in the retrosynthetic analysis (Scheme 19), the macrolactone core was constructed by convergent coupling of fragment C1–C8 ( 90 ) and fragment C9–C20 ( 91 ) using a sequence of Mitsunobu esterification followed by Grubbs' RCM. The synthesis of 1 (Scheme 20) began with the linkage of aldehyde 92 and silyl enol ether 93 mediated by Jacobsen's chiral tridentate chromium( iii ) catalyst 94 .…”
Section: Total Synthesis Of Zampanolide and Dactylolidementioning
confidence: 99%
“…20 As shown in the retrosynthetic analysis (Scheme 19), the macrolactone core was constructed by convergent coupling of fragment C1–C8 ( 90 ) and fragment C9–C20 ( 91 ) using a sequence of Mitsunobu esterification followed by Grubbs' RCM. The synthesis of 1 (Scheme 20) began with the linkage of aldehyde 92 and silyl enol ether 93 mediated by Jacobsen's chiral tridentate chromium( iii ) catalyst 94 .…”
Section: Total Synthesis Of Zampanolide and Dactylolidementioning
confidence: 99%
“…Tetrahydropyrans are the common structural units, which appears in many natural products like tubulexin A [1], (-)-centrolobine [2] and (-)-dactylolide [3]. Especially, tetrahydropyrans having labile group at the 4th position are much useful for the construction of macrocyclic ring system.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, tetrahydropyran derivatives are synthesized by Prins cyclization using an acid catalyst [20][21][22][23]. Alternatively they can be formed by hetero-Diels-Alder cyclization [24][25][26]. In addition it has also been reported that this reaction can be catalyzed by indium halides as Lewis acid [27,28].…”
Section: Introductionmentioning
confidence: 99%